Difusão do saber científico a partir do Museu Itinerante - Travain, Silmar Antonio [UNESP]; França, Mariana da Silva [UNESP]; Fonseca, Antonio Maurício Tannure (Universidade Estadual Paulista (Unesp), 2015)
There are currently a number of social problems that end up highlighting the lack of a balanced public policy. With this, the university extension actions are of great importance for further education and service in community problem solving. Among factors such as technology and the development of new materials, the university may be the integrator agent's knowledge. In this proposal, we developed research prototypes performed by undergraduate and postgraduate workshops and experimental exhibit during a visit of the Traveling Museum - Science Car in Schools and Science Fairs in Ouro Preto / MG and region. In addition to the action with the community in this work we propose to build a link between learning and teaching and give conditions for students of undergraduate courses to gain experience with the workshops. The purpose of this proposal is the dissemination of science in the social inclusion process, providing conditions to increase the scientific literacy among the poorest sections of the population that finds difficulties in access to information.

Existem atualmente, vários problemas sociais que acabam se destacando pela ausência de uma política pública equilibrada. Com isso, as ações extensionistas universitárias são de grande importância por complementar à educação e o serviço na resolução de problemas da comunidade. Entre fatores como a tecnologia e o desenvolvimento de novos materiais, a universidade pode ser o agente integrador do conhecimento. Nesta proposta, desenvolvemos protótipos de pesquisas realizadas por alunos de graduação e de pós-graduação e oficinas experimentais para exposições durante visita do Museu Itinerante – Carro da Ciência em Escolas e Feiras de Ciências em Ouro Preto/MG e região. Além da ação com a comunidade neste trabalho propomos construir uma ligação entre o aprender e o ensinar e dar condições para que alunos dos cursos de graduação ganhem experiência com as oficinas realizadas. O objetivo desta proposta é a divulgação de ciências no processo de inclusão social, proporcionando condições para ampliar a alfabetização científica, entre as camadas mais carentes da população que encontra dificuldades nos acessos a informação.
Keywords: Traveling Museum; Dissemination of knowledge; Physics teaching; Museu Itinerante; Difusão do conhecimento; Ensino de Física